Analysis of Promotional Costs and Location on the Income of MSMEs on Kertabumi Street, Karawang - Hanibah Miftahul Janah Suhardi; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Westscience Press, 2024)
The purpose of carrying out this research is to investigate Promotion Cost Analysis and the location of MSME income on Jalan Kertabumi Karawang. What are the Promotion Costs and Location of MSME players' income on Jalan Kertabumi Karawang. The method used in this research is descriptive qualitative. Based on observations made, there are promotional and location costs that can be utilized by MSME players. The results of this research show that promotional costs and the location of MSME income are on Jalan Kertabumi Karawang. Effective promotional costs can increase customer awareness and interest, and directly influence sales and revenue. Location also plays an important role in MSME income. A strategic location can increase customer accessibility and exposure to a wider market, which can increase sales. There are two methods of promotional costs incurred, namely Online Motorbike Taxi Vouchers and Endorsements. The location on Jalan Kertabumi is a strategic place to set up a business because it is the main access road that is often passed by two-wheeled and four-wheeled drivers. These variables show an increase in the income obtained by MSME players.